Conversion of online purchase intention into actual purchase: The moderating role of transaction security and convenience - Ni Luh Putu Indiani; Gabriel Aprinau Fahik (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Online retail trade in Indonesia has grown dramatically in recent years. However, it is not being followed by an increase in the transaction completion ratio, with a cart abandonment rate of up to 70 percent. This indicates that the transition from online purchase intention to actual purchase is not as simple as postulated in the theory of planned behaviour (TPB); yet, there are other factors moderating the conversion. Therefore, this study aims to develop a model analysing the moderating role of perceived transaction security and convenience in the relationship between online purchase intention and actual purchase. Model development was also motivated by critics regarding TPB's robustness in explaining consumer purchase behaviour; therefore, this model is expected to enrich TPB by providing a more comprehensive picture in online purchase behaviour. The sample consisted of consumers who had shopped for retail products online. The proposed relationship was tested with partial least square method. Results showed that perceived transaction convenience has a positive and significant moderating effect, whereas perceived transaction security showed an insignificant moderating impact. This finding is noteworthy amid risky online purchase environment. Respondents' characteristics and alternative payment methods might explain the insignificant moderation. As a practical implication, it is recommended that online retailers improve online transaction convenience to increase the conversion rate.
Keywords: M31; M30; M21; M15; 650; transaction security; transaction convenience; online purchase intention; actual purchase; online retail industry; online purchase behaviour